Modal Resonant Frequencies and Radiation Quality Factors of Microstrip Antennas. (2nd April 2012) - Eichler, Jan; Hazdra, Pavel; Capek, Miloslav; Mazanek, Milos
Abstract : The chosen rectangular and fractal microstrip patch antennas above an infinite ground plane are analyzed by the theory of characteristic modes. The resonant frequencies and radiation Q are evaluated. A novel method by Vandenbosch for rigorous evaluation of the radiation Q is employed for modal currents on a Rao-Wilton-Glisson (RWG) mesh. It is found that the resonant frequency of a rectangular patch antenna with a dominant mode presents quite complicated behaviour including having a minimum at a specific height. Similarly, as predicted from the simple wire model, the radiation Q exhibits a minimum too. It is observed that the presence of out-of-phase currents flowing along the patch antenna leads to a significant increase of the Q factor.